Combined TMS-fMRI reveals behavior-dependent network effects of right temporoparietal junction neurostimulation in an attentional belief updating task. (28th January 2022) - Mengotti, Paola; Käsbauer, Anne-Sophie; Fink, Gereon R; Vossel, Simone
Abstract: Updating beliefs after unexpected events is fundamental for an optimal adaptation to the environment. Previous findings suggested a causal involvement of the right temporoparietal junction (rTPJ) in belief updating in an attention task. We combined offline continuous theta-burst stimulation (cTBS) over rTPJ with functional magnetic resonance imaging (fMRI) to investigate local and remote stimulation effects within the attention and salience networks. In a sham-controlled, within-subject crossover design, 25 participants performed an attentional cueing task during fMRI with true or false information about cue predictability. By estimating learning rates from response times, we characterized participants' belief updating. Model-derived cue predictability entered the fMRI analysis as a parametric regressor to identify the neural correlates of updating. rTPJ-cTBS effects showed high interindividual variability. The expected learning rate reduction with false cue predictability information by cTBS was only observed in participants showing higher updating in false than in true blocks after sham. cTBS modulated the neural signatures of belief updating, both in rTPJ and in nodes of the attention and salience networks. The interindividual variability of the behavioral cTBS effect was related to differential activity and rTPJ connectivity of the right anterior insula. These results demonstrate a crucial interaction between ventral attention and salience networks for belief updating.